Towards a New Quantum Model of Mass Evolution through Symmetry Breaking (Global Journal of Science Frontier Research, 2025)
The phenomenon of symmetry breaking has remained a significant and widely discussed topic in physics over the past few decades It has been postulated that the mass of the universe evolved from the spontaneous breaking of symmetry in the atoms or molecules of baryonic matter However no concrete theory or model currently exists in the literature that can explain the mechanism of symmetry breaking in a tripartite manner that is in regard to physics mathematics and topology despite substantial research efforts A major problem in physics arises from the inconsistency t hat while the volume or size of atoms and molecules is approximated as three-dimensional spheres the dimension of mass remains non-deterministic In this research article a topological quantum model logically grounded in the philosophies of both mathematics and physics is presented to reveal the mechanism of the evolution of mass from spherically symmetrical atoms and molecules The dimensional form of mass in relation to the fundamental dimension of length L in physics is evaluated here Furthermore the classical principle of conservation of momentum is reinterpreted in terms of mass and volume and a mathematical relationship between these two variables is established through the universal parameter
Keywords: physics; mathematics; and topology—despite substantial research efforts